Generational Renewal through Entrepreneurial Training in the Coffee Zone of Northern Tolima - Rivera González, Miguel Ángel; Rubiano Aranzales, Edicson (Cooperativismo & Desarrollo, 2014)
The project for generational renewal for the sustainability of coffee culture in northern Tolima began as a strategy designed by the Coffee Growers Cooperative of Northern Tolima (Cooperativa de Caficultores del Norte del Tolima, Cafinorte), aimed at stopping the mass migration of young farmers to the cities. It promotes participation by the rural community, particularly students, in the building and cohesion of the social fabric. It does so through a process of education and training in which young people discover the potential opportunities that their farms can provide as organizations and companies. The context in which the research is carried out is determined by the radius of action of the cooperative in the municipalities of Fresno, where the head office of Cafinorte is located, and in Herveo, Palocabildo and Falán in the department of Tolima. The process for learning entrepreneurship consists of education and training in associative culture and solidarity entrepreneurship with support from the rural schools in the area of influence of the cooperative. The goal is to change paradigms learned from their parents to enable them to interpret their reality and find possible alternatives that would make their farms productive.
Keywords: coffee culture; entrepreneurship; training; business mentality; generational relief.